Perceptions and experiences of female nurses when confronted with expressing a conscientious objection towards end-of-life care in Greece - Polychronis Voultsos; Christina-Erato Zymvragou; Nikolaos Raikos (BMC, 2023)
Abstract Background Conscientious objection in nursing has been a topic of much discussion in recent years. Healthcare providers' conscientious objection has been included in Greek legislation. However, little is known about the real experiences of nurses who want to apply conscientious objections in their practice. This study aimed to contribute to filling that gap. Methods This qualitative study was conducted with eighteen experienced female nurses. Data were collected through semi-structured in-depth qualitative interviews conducted with purposively selected nurses during the period from October 2019 to January 2020. Interviews were transcribed verbatim and analysed thematically. The ethical principles of anonymity, voluntary participation and confidentiality were considered. Results Eight major themes and seven subthemes emerged from the thematic data analysis. Oppressive behaviors in the workplace and subservient interactions between nurses and physicians, suboptimal communication and inadequate support of nurses, perceived ineffectiveness of nurses' conscientious objections, missing legal protection against job insecurity, provision of care labeled 'futile', nurses' false knowledge and perceptions on medical situations related to conscientious objections, nurses' fears of isolation bullying and negative gossip in the workplace and a trivial amount of nurses' involvement in medical decisions emerged as barriers to nurses raising conscientious objection. Furthermore, from data analysis, it emerged that some nurses had false knowledge and perceptions on medical situations related to conscientious objections, some nurses experienced mild uncertainty distress about their ethical concerns, nurses considered their remote contribution as participation that can give rise to conscientious objection, a collective conscientious objection raised by nurses might have increased chances of being effective, and upbringing, childhood experiences, education and religion are factors shaping the nurses' core values. Conclusion A total of fifteen themes and subthemes emerged from this study. Most of the findings of this study were previously unknown or undervalued and might be helpful to inform nurses and nursing managers or leaders as well as healthcare policy makers. The results of this study might contribute to addressing the need for creating ethically sensitive health care services and ensuring nurses' moral integrity and high quality of patient care.